2020
DOI: 10.3390/ma13133041
|View full text |Cite
|
Sign up to set email alerts
|

Green and Durable Lightweight Aggregate Concrete: The Role of Waste and Recycled Materials

Abstract: Lightweight aggregate concrete manufactured by solid waste or recycled by-products is a burgeoning topic in construction and building materials. It has significant merits in mitigating the negative impact on the environment during the manufacturing of Portland cement and reduces the consumption of natural resources. In this review article, the agricultural and industrial wastes and by-products, which were used as cementitious materials and artificial lightweight aggregate concrete, are summarized. Besi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 120 publications
(183 reference statements)
0
12
0
Order By: Relevance
“…Concrete made from ceramic wastes can address a number of environmental issues. [8] When ceramic powder used in specified amounts to replace OPC, ceramic waste powder is very successful in lowering environmental hazards (e.g., land pollution). Where conventional concrete strength is suggested, this waste can be used in the concrete.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Concrete made from ceramic wastes can address a number of environmental issues. [8] When ceramic powder used in specified amounts to replace OPC, ceramic waste powder is very successful in lowering environmental hazards (e.g., land pollution). Where conventional concrete strength is suggested, this waste can be used in the concrete.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lightweight aggregates from waste materials, such as demolition wastes and agricultural residues, can be used to produce lightweight concrete blocks and achieve a lower thermal conductivity (Callejas et al, 2017). Agricultural solid waste from maize and corn has been incorporated with cementitious powder to prepare lightweight concrete (Wang et al, 2020). The National Concrete Masonry Association suggested that the thermal resistance of lightweight concrete blocks is less sensitive to the thickness of blocks compared to normal weight blocks (NCMA, 2013).…”
Section: Concrete Blocks and Clay Bricksmentioning
confidence: 99%
“…In the past, a few researchers have tried to produce structurally lightweight concrete by using different materials as a replacement of normal coarse aggregates, i.e., expanded polystyrene (EPS) lightweight aggregate, organic lightweight aggregate, solid waste or recycled by-products and expanded clay aggregates [ 1 , 2 , 3 , 4 ]. A detailed experimental study was conducted to precisely estimate the compressive strength of structural lightweight concrete produced by using different types of expanded clays [ 5 ].…”
Section: Introductionmentioning
confidence: 99%